The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1071/ch9841607
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and vibrational spectra of some tris(alkanethiolato)mercurate(II) complexes, and crystal structure of the Hexakis(methanethiolato)dimercurate(II) dianion

Abstract: The complexes [cation] [Hg(SR)3](R = Me, cation = Et4N+; R = But, cation = Et4N+, Bu4N+, [N(Ph3P)2]+) have been prepared. The crystal structure of the methanethiolate complex shows that it contains centrosymmetric dinuclear anions [(MeS)2Hg(�-SMe)2Hg(SMe)2]2- with distorted tetrahedral geometry about the mercury atoms. Vibrational spectroscopic evidence suggests that this complex dissociates on dissolution in ethanol to give mononuclear [Hg(SMe)3]- species. The ButS- complexes appear to exist as mononuclear [H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 0 publications
5
26
0
Order By: Relevance
“…However, in the current study, EXAFS spectra were obtained for solutions A1 and A2 at room temperature in a wide k -range (up to 14.5 Å −1 ) and no such Hg⋯Hg scattering contribution could be observed (Figure S-4). In a survey of the Cambridge Structural Database (CSD, version 5.31, Nov. 2009) (35), we found dimeric complexes (such as COHWEB and DAXRAV) with two bridging thiolate groups, Hg 2 (μ-SR) 2 , leading to Hg II ⋯Hg II distances of ~ 3.6 Å (36, 37). Single oxygen bridges between two mercury(II) atoms have been found in several crystal structures, leading to Hg II ⋯Hg II distances of 3.5–3.6 Å (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the current study, EXAFS spectra were obtained for solutions A1 and A2 at room temperature in a wide k -range (up to 14.5 Å −1 ) and no such Hg⋯Hg scattering contribution could be observed (Figure S-4). In a survey of the Cambridge Structural Database (CSD, version 5.31, Nov. 2009) (35), we found dimeric complexes (such as COHWEB and DAXRAV) with two bridging thiolate groups, Hg 2 (μ-SR) 2 , leading to Hg II ⋯Hg II distances of ~ 3.6 Å (36, 37). Single oxygen bridges between two mercury(II) atoms have been found in several crystal structures, leading to Hg II ⋯Hg II distances of 3.5–3.6 Å (38).…”
Section: Discussionmentioning
confidence: 99%
“…From studies in which the 13C chemical shifts were measured as a function of the Hg(I1):GSH ratio at constant pH, it was shown that the differences are due to formation of the 3:l complex, Hg(g1~tathione)~. Evidence for the formation of Hg(SR)3-complexes, where R represents methyl and tert-butyl groups, in solution has also been obtained from vibrational spectroscopic studies (13). In another study, the crystalline mononuclear, three-coordinate mercury(I1) thiolate [NBun4:I [Hg(SPh)3] was prepared and its crystal structure determined (14).…”
Section: Methodsmentioning
confidence: 99%
“…4 to eq. [13] using nonlinear least-squares curve-fitting methods. The values used for (YRSH~SR, (YR'SH~SR,, (YRSH, and a,,,, in the curve fitting were calculated directly from sobs measured for solutions containing only these species.…”
Section: Displacement Equilibrium Constantsmentioning
confidence: 99%
“…With dithiolate ligands, an infinite chain of [H~,(scH,cH~s),]~-dianions is formed by 1,2-dithiolatoethane (47), while trans-l,2-dithiolatocyclohexane forms a dinuclear complex with Hg2S, core (48). Hg(SCH2-CH,CH2CH3), crystallizes with two HgS, tetrahedra linked by edge and corner sharing into helical chains (49), and the [H~~(scH,),]'-ion forms a centrosymmetric, doubly bridged dimer (50). Hg3S, cores are known (47,51), as are eightmembered Hg4S4 rings (43,52 For personal use only.…”
Section: The Synthesis Of the Hg Salt [(P-sc6h5)6{hgp(c6h5)3}mentioning
confidence: 99%
“…Bridging thiolate ligands are common, with a wide range of Hg-S distances. A search of the CSD (34) yielded thirteen entries describing a total of fifteen structures with (p2-SR) ligands (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). The structures of the complexes and geometries of the Hg-S-Hg bridges q e summarised in Table 5.…”
Section: The Synthesis Of the Hg Salt [(P-sc6h5)6{hgp(c6h5)3}mentioning
confidence: 99%